2000
DOI: 10.1016/s0370-1573(99)00045-9
|View full text |Cite
|
Sign up to set email alerts
|

Searches for invisible axions

Abstract: The axion+ hypothetical elementary particle, emerged from a compelling solution to the Strong-CP problem in &CD. Subsequently, the axion wee recognized to be a good Cold Dark Matter candidate. Although dark matter axions have only feeble couplings to matter end radiation, extremely sensitive searches are underway around the world. We review the state of experiments searching for the axion through its coupling to photons. Besides answering an outstanding question in particle physics, the discovery of dark matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
136
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 60 publications
1
136
0
1
Order By: Relevance
“…Let us first calculate the contribution γ add z,1 into γ add z which originates from the first and third terms on the righthand side of Eq. (12). For these terms, the integration with respect to τ in Eq.…”
Section: Additional Force Arising From the Exchange Of Two Ax-ionmentioning
confidence: 99%
“…Let us first calculate the contribution γ add z,1 into γ add z which originates from the first and third terms on the righthand side of Eq. (12). For these terms, the integration with respect to τ in Eq.…”
Section: Additional Force Arising From the Exchange Of Two Ax-ionmentioning
confidence: 99%
“…They put severe constraints on axion-matter coupling in different axion mass ranges. A detailed review of axion studies can be found in [5,6].The recently reported positive results of the PVLAS experiment on light polarization rotation in a vacuum in the presence of a transverse magnetic field [7] may be seen as evidence of the long sought axion [8]. According to [7], the mass of neutral boson possibly responsible for the observed signal is 1 < M A < 1.5 meV.…”
mentioning
confidence: 97%
“…Furthermore, the axion-photon mixing has been applied to explain several physical puzzling observations, for example to explain large scale polarization alignment in * ptiwari@physics.technion.ac.il distant quasars [27,[47][48][49][50][51], polarization properties of radio galaxies [11,19,52] and the dimming of distant supernovae [16,19,21]. In addition there are various experiments looking for direct and indirect observations of axions [12,22,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%